Nilai-nilai Pendidikan Akhlak dalam Kitab Bulūg Al-marām min Adillah Al-aḥkām Karya Ibnu Ḥajar Al-`asqalānī dan Relevansinya dengan Pendidikan Karakter - Irpan Supriatna; Sopa Sopa; Saiful Bahri; Suharsiwi Suharsiwi (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2023)
Bulughul Maram Min Adilatil Ahkam is a book compiled by Ibn Hajar Al-Asqalani (773 H - 852 H). This book is a thematic hadith book that contains traditions that are used as sources for taking fiqh law (istinbath) by fiqh experts, because almost all of the hadiths are related to fiqh law. However, the last part of the book Bulughul Maram is a collection of hadiths about adab and morals called Kitabul Jami '. The aims of this study are: (1) to determine the values of moral education contained in the book Bulughul Maram, (2) to determine the relevance of the values of moral education in the book Bulughul Maram with Character Education. The research method used by the author is a type of document analysis research through library research, by collecting data or materials related to the theme of the discussion and its problems, which are taken from library sources, then analyzed by content analysis methods. This analysis examines the values of moral education from the contents of the book Bulughul Maram. To support this research, the author uses the main data source, namely, the book of Hadith Bulughul Maram by Imam Ibn Hajar Al-Asqalani and a secondary source in the form of syarah from the book. Based on the results of this study, the author categorizes the hadiths of morality in the book Bulughul Maram into three parts, namely: morality to Allah Ta'ala, morality to oneself, and morality to family. Then the author concludes that in the book there are hadiths that contain the values of moral education whose relevance can improve character education which is only based on human norms. Because having character is thinking, having wills, and behaving according to their nature (conscience) to continue to serve Allah, they are not only human beings with good character but also have noble character.